2022
DOI: 10.1038/s43016-022-00470-6
|View full text |Cite
|
Sign up to set email alerts
|

Distinct increase in antimicrobial resistance genes among Escherichia coli during 50 years of antimicrobial use in livestock production in China

Abstract: Antimicrobial agents have been used in meat production for decades and its consumption is considered an key driver for the emergence and dissemination of antimicrobial resistance (AMR). However, large-scale studies on AMR changes in animal isolates since the introduction of antimicrobial usage remain scarce. We applied whole genome sequencing analysis to 982 animal-derived Escherichia coli collected in China from 1970s to 2019 and found increasing trends for the presence of numerous antimicrobial resistance ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…Approximately 75% of antibiotics are not absorbed by the animals and are excreted from the body via feces and urine, which can directly contaminate and harm the surrounding environment ( Mackie et al, 2006 ; Zhou et al, 2022 ). Meanwhile, the misuse or overuse of antibiotics in animal production has led to diverse antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs), which can be transferred in animals and humans ( Martin et al, 2015 ; Zhang et al, 2015 ; He et al, 2020 ; Liu et al, 2022 ; Yang et al, 2022 ). There is increasing evidence that antibiotic resistance in humans is mainly related to the wide application of nontherapeutic antibiotics in animals ( Martin et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 75% of antibiotics are not absorbed by the animals and are excreted from the body via feces and urine, which can directly contaminate and harm the surrounding environment ( Mackie et al, 2006 ; Zhou et al, 2022 ). Meanwhile, the misuse or overuse of antibiotics in animal production has led to diverse antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs), which can be transferred in animals and humans ( Martin et al, 2015 ; Zhang et al, 2015 ; He et al, 2020 ; Liu et al, 2022 ; Yang et al, 2022 ). There is increasing evidence that antibiotic resistance in humans is mainly related to the wide application of nontherapeutic antibiotics in animals ( Martin et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multidrug-resistant (MDR) bacteria (including Staphylococcus spp., Enterococcus spp., Salmonella spp., E. coli , etc.) and ARGs were transferred to workers and residents in the surrounding environment via inhalation, thus, posing the risk of diseases ( Bai et al, 2021 ; Jeżak and Kozajda, 2022 ; Yang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Animals, particularly food animals, have long been recognized as important reservoirs for ESBL-producing E. coli isolates ( 21 ). However, little research has been reported about multiple-antibiotic- resistant E. coli in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…We presumed that the ESBL gene-positive isolates were more likely to recruit the resistance genes than isolates without target ESBL genes. Considering that bla CTX-M-55 has become increasingly prevalent in ESBL-producing E. coli isolates of animal origin but is relatively rare in isolates of human origin, this finding might indicate that bla CTX-M-55 and a variety of drug resistance genes emerged and rose under antibiotic selective pressure in animal husbandry ( 21 ). Therefore, prohibiting or strictly curtailing antimicrobial use in animal husbandry is urgently needed to address the increasing threat of antimicrobial resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The misuse and overuse of antibiotics, as the key driving force in the evolution and propagation of antibiotic resistance genes (ARGs), has caused ecological and human health risks, attracting the global attention (1)(2)(3). As the selection pressure posed by antibiotics was not strictly specific, long-term exposure to single or several antibiotics, especially those used widely and extensively, could accelerate the co-evolution of multiple ARGs (4)(5)(6). Amphenicol antibiotics, include chloramphenicol (CAP), its congener thiamphenicol (TAP) and florfenicol.…”
Section: Introductionmentioning
confidence: 99%